Intergenic Polycomb target sites are dynamically marked by non-coding transcription during lineage commitment - Hekimoglu-Balkan, Betül (Landes Bioscience, 2012)
Non-coding (nc) RNAs are involved both in recruitment of vertebrate Polycomb (PcG) proteins to chromatin, and in activation of PcG target genes. Here we investigate dynamic changes in the relationship between ncRNA transcription and recruitment of PcG proteins to chromatin during differentiation. Profiling of purified cell populations from different stages of a defined murine in vitro neural differentiation system shows that over 50% of regulated intergenic non-coding transcripts precisely correspond to PcG target sites. We designate these PcG recruiting elements as Transcribed Intergenic Polycomb (TIP) sites. The relationship between TIP transcription and PcG recruitment switches dynamically during differentiation between different states, in which transcription and PcG recruitment exclude each other, or in which both are present. Reporter assays show that transcribed TIP sites can repress a flanking gene. Knockdown experiments demonstrate that TIP ncRNAs are themselves required for repression of target genes both in cis and in trans. We propose that TIP transcription may ensure coordinated regulation of gene networks via dynamic switching and recruitment of PcG proteins both in cis and in trans during lineage commitment.